Analysis of unusual climatic characteristics of precipitation and four typical extreme weather processes in China in 2021 - Xiaokang WANG; Hao YANG; Chunguang CUI; Chao LI; Haixia QI; Muyun DU; Jingyu WANG; Xiaofang WANG (暴雨灾害, 2022)
In 2021, the weather situations are complex,the climate anomaly is significant,and extreme events occur frequently in China. This paper briefly reviews the abnormal characteristics of the main flood season over China and Huaxi Autumn Rain,and makes a preliminary analysis of four high impact weather processes in Henan and Hubei. The results show that the mean precipitation over China from April to October 2021 was 7.8% more than its normal value,specifically 100% more than that in some areas such as Henan,Hebei and Shanxi Province. Under the influence of the external forcing factor "La Nina" abnormal SST,the water vapor in the periphery of the subtropical high and the cold air in the north were very active,the Huaxi Autumn Rain broke the historical record since 1961. The "21.7" rainstorm in Henan Province occurred under the background of typhoon,vortex,shear line and convergence line. A large amount of water vapor from the Northwest Pacific appeared in front of the mountain under the coupling of low-level jet and boundary layer jet,dynamic blocking uplift and thermal uplift of terrain. Under the favorable multi-scale circulation background,the interaction between the terrain and the convergence zone of low-level wind field triggered convection,maintained the precipitation in the narrow and long valley terrain,and triggered the "8.12" heavy precipitation in Suizhou Hubei Province. The merging and strengthening of meso-γ scale strong convective cells caused two convective gale events in Wuhan. The sudden enhanced horizontal wind in the middle layer triggered the sinking movement,and the falling created the local strong cold pool and the extreme gale on the ground.